The Role of Clean Hydrogen Value Chain in a Successful Energy Transition of Japan - Mohsen Salimi; Morteza Hosseinpour; Tohid N.Borhani (Energies, 2022)
The clean hydrogen in the prioritized value chain platform could provide energy incentives and reduce environmental impacts. In the current study, strengths, weaknesses, opportunities, and threats (SWOT) analysis has been successfully applied to the clean hydrogen value chain in different sectors to determine Japan’s clean hydrogen value chain’s strengths, weaknesses, opportunities, and threats as a case study. Japan was chosen as a case study since we believe that it is the only pioneer country in that chain with a national strategy, investments, and current projects, which make it unique in this way. The analyses include evaluations of clean energy development, power supply chains, regional energy planning, and renewable energy development, including the internal and external elements that may influence the growth of the hydrogen economy in Japan. The ability of Japan to produce and use large quantities of clean hydrogen at a price that is competitive with fossil fuels is critical to the country’s future success. The implementation of an efficient carbon tax and carbon pricing is also necessary for cost parity. There will be an increasing demand for global policy coordination and inter-industry cooperation. The results obtained from this research will be a suitable model for other countries to be aware of the strengths, weaknesses, opportunities, and threats in this field in order to make proper decisions according to their infrastructures, potentials, economies, and socio-political states in that field.